2016
DOI: 10.1055/s-0036-1578805
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following Laminoplasty or Laminectomy and Fusion in Patients with Myelopathy Caused by Ossification of the Posterior Longitudinal Ligament: A Systematic Review

Abstract: Study Design Systematic review. Objective To compare laminoplasty versus laminectomy and fusion in patients with cervical myelopathy caused by OPLL. Methods A systematic review was conducted using PubMed/Medline, Cochrane database, and Google scholar of articles. Only comparative studies in humans were included. Studies involving cervical trauma/fracture, infection, and tumor were excluded. Results Of 157 citations initially analyzed, 4 studies ultimately met our inclusion criteria: one class of evidence (CoE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
1
32
0
4
Order By: Relevance
“…In particular, the rates of intraoperative dural leaks and postoperative C5 palsy have both been reported to be higher in patients with OPLL compared to other DCM pathologies [21,71]. These complications may be specific to certain approaches, however, with rates of DT being higher with anterior approaches and C5 palsy being higher with LF posterior approaches [30,31,33,37]. Several techniques specific to OPLL surgeries have been developed to combat the incidence of these complications including the ADF and the ACAF procedures [24,41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the rates of intraoperative dural leaks and postoperative C5 palsy have both been reported to be higher in patients with OPLL compared to other DCM pathologies [21,71]. These complications may be specific to certain approaches, however, with rates of DT being higher with anterior approaches and C5 palsy being higher with LF posterior approaches [30,31,33,37]. Several techniques specific to OPLL surgeries have been developed to combat the incidence of these complications including the ADF and the ACAF procedures [24,41].…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by less aggressive tissue disruption than that associated with LF, and can be performed using one of several different techniques [32]. The lack of instrumented fusion and laminectomy make the LAMP procedures better for preserving cervical ROM [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Surgical treatment is need because it usually lead to progressive and stepwise deterioration of neurologic function. [ 2 ] Surgical treatment with either anterior or posterior approaches can result in satisfactory clinical results. [ 3 ] When ≥3 segments are involved, the complication rates associated with anterior surgery accelerate.…”
Section: Introductionmentioning
confidence: 99%
“…However, OPLL is different from other etiological factors of myelopathy with respect to neck ROM that may incite further progression of OPLL. [ 67 ] In general, laminoplasty results in long-term decrease in ROM due to unintended autofusion along the lateral margins of the laminoplasty. [ 4 ] It is suggested that progression of OPLL is stimulated by the dynamic factors and ROM stabilization may reduce the progression of OPLL.…”
Section: Discussionmentioning
confidence: 99%